The importance of reflection and self-assessment in modern education - Najmutdinova, Gulnozakhon Bakhtiyorovna (The Lingua Spectrum, 2026)
This article examines the importance of reflection and self-assessment in modern education. Reflection is considered as a key process that helps learners analyze their learning experiences, knowledge, and achievements. Self-assessment encourages students to take responsibility for their learning, develop independence, and enhance critical thinking skills. The article highlights the role of reflective practices in improving motivation, academic performance, and personal growth. In addition, teacher reflection is discussed as an essential factor for professional development and improving the quality of education. The study concludes that reflection and self-assessment are effective pedagogical tools for implementing a competency-based approach in contemporary educational systems.